2014
DOI: 10.1159/000355803
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Hepatitis C Virus in Dialysis Population

Abstract: Hepatitis C virus (HCV) infection remains common among patients undergoing regular dialysis and good evidence supports the detrimental role of HCV on survival in patients undergoing maintenance dialysis. According to an updated meta-analysis of clinical studies (n=15; 195,370 unique patients on maintenance dialysis), the summary estimate for adjusted relative risk (all-cause mortality) with anti-HCV across the published studies was 1.32 with a 95% Confidence Intervals of 1.24; 1.42, homogeneity assumption was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
(66 reference statements)
0
25
0
Order By: Relevance
“…10 Recent studies suggest that HCV-infected patients with CKD have an accelerated rate of kidney function loss and an increased risk of progressing to ESRD. [14][15][16][17][18][19] In one study, Molnar et al 19 showed that HCVinfected patients with CKD had an increased mortality and an accelerated rate of progression to ESRD, raising the important question of whether treating to obtain a sustained virologic response defined as an undetectable viral load 12 weeks after completion of treatment (SVR12) would diminish the rate of decline in GFR.…”
Section: Hcv In Patients With Kidney Diseasementioning
confidence: 99%
“…10 Recent studies suggest that HCV-infected patients with CKD have an accelerated rate of kidney function loss and an increased risk of progressing to ESRD. [14][15][16][17][18][19] In one study, Molnar et al 19 showed that HCVinfected patients with CKD had an increased mortality and an accelerated rate of progression to ESRD, raising the important question of whether treating to obtain a sustained virologic response defined as an undetectable viral load 12 weeks after completion of treatment (SVR12) would diminish the rate of decline in GFR.…”
Section: Hcv In Patients With Kidney Diseasementioning
confidence: 99%
“…1 In developed countries, approximately 1.8% to 8% of the kidney transplant recipients are infected with HCV. 2,3 Hepatitis C virus infection has negative effects on both patient and graft survival.…”
Section: Introductionmentioning
confidence: 99%
“…14,22 The most frequent extrahepatic complications are de novo or recurrent glomerular disease and new-onset diabetes mellitus. 1 Hepatitis C virus-related liver disease after kidney transplant The risk of developing posttransplant liver disease depends on the severity of the liver disease before transplant, liver pathology, coinfection with hepatitis B virus, and the immunosuppressive regimen. 9 Immunosuppression could promote viral replication in hepatocytes, enhancing the progression of liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, stratified analysis showed that the adjusted relative risk (aRR) for cardiovascular mortality with anti-HCV was 1.26 (95% CI, 1.10; 1.45) [6]. Studies are in progress to deepen our understanding of the link between HCV and cardiovascular risk among patients on maintenance dialysis [7].…”
Section: Introductionmentioning
confidence: 99%